Impact of COVID-19 restrictions on men’s mental health services in Australia - Guntuku, Shravankumar; Hall, Neil; Poole, Glen (Archives of Men’s Health, 2020)
Introduction: Mental health services in Australia have faced significant challenges during the COVID-19 pandemic in adopting the new changes to reach service users. The rapid changes in the situation and surge in the number of people seeking help or in crisis have led services to use many strategies which they would not have considered in normal situations. The services working with men were especially experiencing the difficulty in fulfilling the needs of their clients as the evidence shows that Australian men’s help seeking behaviour is lower than women. Materials and Methods: A survey was conducted online to ascertain the level of impact on their services, their client groups and the lessons learned during online service delivery. The survey was conducted by Australian Men’s Health Forum with 20 questions, both with multiple choice and narrative answer options. Results: In total, 53 male-specific services have responded. 81% made changes to their services; 43% enabled their staff and volunteers to work from home; 84% adopted strategies to conduct their meeting virtually with clients. Conclusion: Most services made significant changes such as phone/video counselling, but felt that this cannot be the norm post-pandemic as it lacks the empathic human touch to service delivery. Innovative strategies were developed to reach men living in remote/rural areas with no cost or travel time. However, there are many concerns about vulnerable groups such as older adults, Aboriginal and Torres Strait Islanders and men living in remote areas, who have limited access to electronic devices and reliable internet access. Implications: These findings have implications for reorienting frontline health services, particularly in times of widespread crisis when service delivery models need to change. There is, therefore, a direct consequence for building healthy public policy in relation to the health of men and boys from marginalised/vulnerable groups that incorporates healthy environments and positive social connections.